Consumers acceptance towards CKS Supermarket in Donggongon Penampang / Regina M. Fredoline Sikain - Fredoline Sikain, Regina M. (2006)
Consumers' perception and attitude are part of the psychological factors that affect consumer behaviour leading to buying decisions. It is one of the well-studied fields of relationship marketing. This study is important as it gives initial understanding and indication of how consumers perceived marketing offers that influence their purchasing behaviours. It is crucial information that can help to create an effective marketing mix that would assure customer satisfaction. In this study entitled, "Consumers' Acceptance toward.CKS Supermarket in Donggongon Penampang" its main aim is to identify how consumers perceived CKS Supermarket and their initial attitude towards this supermarket, which will determine their acceptance of the supermarket. By understanding their acceptance of the supermarket, it would be easier to determine the best marketing approach to cater the consumers' needs and demands. From this study, it was found that the main factor that shows positive acceptance of the supermarket is the location of the supermarket, whereby 97.3% agreed that CKS is strategically located. However, other factors that did not show favorable consumers' acceptance of the supermarket are: parking space, availability of varied products especially imported foods and fresh produce, organization of items on display and also the price of items as compared to other shopping outlets, especially Servay. It was also noted that majority of the respondent rated CKS Supermarket as average (70.7%) and good (24.0%). Findings from this study would be beneficial to CKS management in order for them to formulate an effective marketing mix and ensuring that the marketing environment is conducive for shopping.